Exploring Innovative Music Teaching Management Systems: A Systematic Literature Review - Tania Ayu Sekar Arum; Deden Witarsyah Jacob (Jurnal Syntax Admiration, 2024)
This systematic literature review explores innovative music teaching management systems (MTMS) to understand current trends, technological advancements, and pedagogical approaches. The review synthesizes findings from various studies, focusing on how MTMS facilitate effective music education through digital tools, platforms, and methodologies. It highlights key innovations such as interactive software, online learning environments, and mobile applications that enhance both teaching and learning experiences. Additionally, the review examines the integration of artificial intelligence and machine learning in personalizing music education, providing adaptive feedback, and fostering student engagement. The pedagogical implications of these technologies are considered, emphasizing their role in supporting differentiated instruction and accommodating diverse learning styles. Furthermore, the review addresses the challenges and limitations associated with implementing MTMS, including issues of accessibility, teacher training, and the digital divide. The findings suggest that while MTMS offer significant potential for enriching music education, successful implementation requires a holistic approach that includes adequate infrastructure, professional development, and continuous evaluation. This review contributes to the field by providing a comprehensive overview of current MTMS innovations and their impact on music education, offering insights for educators, researchers, and policymakers aiming to enhance the quality and accessibility of music instruction through technology.